Preparation method of coal rock polished section
By pre-wetting the coal particles, the problem of low flatness of the light sheet in the traditional coal rock sheet preparation method is solved, and a higher quality coal rock sheet preparation is achieved, which is suitable for modern instrument analysis.
Patent Information
- Application Number
- CN202411798646.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
AI Technical Summary
Traditional coal rock light sheet preparation methods lead to a large number of bubbles inside the light sheet, many potholes on the surface, and low flatness, which limits its application and analysis accuracy in modern instrument analysis.
Before the coal particles are mixed with the binder, pre-wetting treatment is carried out, and the coal particles are fully wetted with water or dextrin solution to eliminate the gas film on the surface of the coal particles, thereby avoiding the generation of internal bubbles.
Through pre-wetting treatment, the flatness and finish of the coal rock light sheet is significantly improved, the surface pits are eliminated, the microscopic composition boundaries are clear, and the quality and analysis accuracy of the light sheet are improved.
Smart Images

Figure CN119643245A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a coal rock optical slice, and belongs to the technical field related to coal rocks. Background Art
[0002] Coal rock sections, also known as coal particle cementation sections or pulverized coal brick sections, are a type of coal particle sections used for coal petrology research under reflected light. Coal petrology research mainly measures the microscopic components, mineral composition, microstructure and coalification degree of coal, and is widely used in coal quality evaluation, coal blending and coking, coalfield geological research, etc. The traditional use of coal rock sections is mainly to use optical microscopes to conduct qualitative detection and quantitative statistics of organic microscopic components and mineral components in coal based on reflection color, protrusions, morphology and surface structure. With the development of testing technology, coal rock sections have been widely used in the micro-area analysis of minerals in coal. For example, the microscopic component structure, mineral particle material composition, element occurrence state, etc. in coal are measured using scanning electron microscope energy spectrometer, electron probe, atomic force microscope and other analytical methods. However, the coal rock slices produced by traditional preparation methods are prone to contain a large number of bubbles inside, resulting in many pits on the surface of the slices, and the smoothness and flatness are not high. This has a negligible impact when observing using an optical microscope, but it will limit the application of coal rock slices in modern instrumental analysis and affect the analysis accuracy.
[0003] Previous researchers proposed improved methods based on the traditional preparation methods of coal rock slices. For example, water-abrasive sandpaper and a more widely applicable polishing liquid were used to optimize the grinding process during the polishing process, and a new grinding method with fast, strong adaptability and ideal effect was obtained. The complete preparation process of special coal rock slices such as fragile samples, aged block coal slices, and aged powdered coal slices is mainly to cast the slices after heating and boiling the rosin + paraffin combination with secondary cold glue. After polishing, a coal slice with a smooth surface and clear boundaries of microscopic components can be obtained. Using epoxy resin E-44 as a binder to prepare coal rock slices can shorten the experimental time, reduce the experimental cost, and improve the experimental success rate. Epoxy resin and epoxy curing agent were selected as binders, and negative pressure degassing technology was used to prepare coal rock slices with a relatively smooth surface.
[0004] The above methods have been improved by improving the grinding method, the type of adhesive, etc., but these methods are difficult to completely solve the problem of insufficient surface flatness of the optical sheet. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a coal rock sheet. By pre-wetting the coal particles and then preparing the coal rock sheet, the problem of low flatness of the coal rock sheet is solved, and a more reliable new method for preparing the coal rock sheet is provided for coal petrology research and testing.
[0006] The technical solution of the present invention is a method for preparing a coal rock slice. The coal sample crushed to a qualified particle size is pre-moistened with water or a dextrin solution before being mixed with a binder, and the coal particles are stirred to fully moisten the coal particles. The coal particles are then filtered and dried in the shade and then mixed with the binder. The coal rock slice is prepared by drying in a mold at room temperature and then grinding and polishing.
[0007] In the aforementioned method for preparing a coal rock optical film, when water is used to pre-wet the coal sample, 2 to 5 mL of water is added to 1 g of the coal sample.
[0008] In the aforementioned method for preparing a coal rock optical film, when water is used to pre-wet the coal sample, 1 g of the coal sample is weighed and 5 mL of water is added accordingly.
[0009] In the aforementioned method for preparing a coal rock slice, when the coal sample is pre-moistened with a dextrin solution, 1 gram of the coal sample is weighed, and 5 mL of water and 50 to 300 mg of dextrin are added accordingly, and the water and dextrin together form a dextrin solution.
[0010] In the aforementioned method for preparing a coal rock optical film, when the coal sample is pre-moistened with a dextrin solution, 1 g of the coal sample is weighed, and 5 mL of water and 150 mg of dextrin are added accordingly, and the water and dextrin together form a dextrin solution.
[0011] Beneficial effects of the present invention: Compared with the prior art, the present invention adopts the above-mentioned technical solution. Compared with the national standard method, the coal rock slices prepared by this method are of higher quality, with a flat and smooth polished surface, no pits on the surface, and clear boundaries of microscopic components. During the pretreatment process, water molecules and dextrin molecules are adsorbed on the surface of coal particles, which enhances the surface wettability of coal particles and eliminates the air film on the surface of coal particles, thereby avoiding the generation of internal bubbles during the film making process. Among them, the quality of coal rock slices prepared by pretreatment with a dextrin solution formed by water and dextrin is higher than that of coal rock slices pretreated only with water. This method has simple steps and strong operability, improves the qualified rate of slices, and does not affect the properties of coal rocks. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a schematic diagram of the process of preparing the coal rock optical slice of the present invention;
[0013] Figure 2 Schematic diagram of the effect of water and dextrin dosage on the surface smoothness of the polished surface of coal rock slices (Figure a is S a , S q , S z ; Figure b is S dr );
[0014] Figure 3 It is the two-dimensional morphology, 3D morphology and corresponding 3D morphology contour map of the untreated coal rock optical section (Figure a);
[0015] Figure 4-Figure 6 The two-dimensional morphology, 3D morphology and corresponding 3D morphology contour diagram of the coal rock light slices (Figure b, Figure c, Figure d) prepared by water pretreatment (Figure b uses 0.5 mL / g of water; Figure c uses 2 mL / g of water; Figure d uses 5 mL / g of water);
[0016] Figure 7-Figure 9 The two-dimensional morphology, 3D morphology and corresponding 3D morphology contour diagram of coal rock light slices (Figure e, Figure f, Figure g) prepared by pretreatment with dextrin solution (Figure e uses 5 mL / g water and 50 mg / g dextrin; Figure f uses 5 mL / g water and 150 mg / g dextrin; Figure g uses 5 mL / g water and 300 mg / g dextrin);
[0017] Fig.10 Mechanism diagram of pre-wetting of coal particles without treatment (a) and with dextrin solution (b). DETAILED DESCRIPTION
[0018] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to limit the present invention.
[0019] Embodiment 1 of the present invention: A method for preparing a coal rock sheet, wherein the coal sample crushed to a qualified particle size is pre-moistened with water before being mixed with a binder, stirred to fully wet the coal particles, filtered and dried in the shade, and then mixed with the binder, placed in a mold and dried at room temperature, and then ground and polished to prepare a coal rock sheet. 1g of coal sample is weighed and 2mL of water is added accordingly.
[0020] Embodiment 2 of the present invention: A method for preparing a coal rock sheet, wherein the coal sample crushed to a qualified particle size is pre-moistened with water before being mixed with a binder, stirred to fully wet the coal particles, filtered and dried in the shade, and then mixed with the binder, placed in a mold and dried at room temperature, and then ground and polished to prepare a coal rock sheet. 1g of coal sample is weighed and 5mL of water is added accordingly.
[0021] Embodiment 3 of the present invention: A method for preparing a coal rock sheet, wherein the coal sample crushed to a qualified particle size is pre-moistened with a dextrin solution before being mixed with a binder, and the coal particles are stirred to fully moisten the coal particles, and then mixed with the binder after filtration and shade drying, and then placed in a mold and dried at room temperature, and then ground and polished to prepare a coal rock sheet. 1g of the coal sample is weighed, and 5mL of water and 50mg of dextrin are added accordingly, and the water and dextrin together form a dextrin solution.
[0022] Embodiment 4 of the present invention: A method for preparing a coal rock sheet, wherein the coal sample crushed to a qualified particle size is pre-moistened with a dextrin solution before being mixed with a binder, and the coal particles are stirred to fully moisten the coal particles, and then mixed with the binder after filtration and shade drying, and then placed in a mold and dried at room temperature, and then ground and polished to prepare a coal rock sheet. 1g of the coal sample is weighed, and 5mL of water and 150mg of dextrin are added accordingly, and the water and dextrin together form a dextrin solution.
[0023] Embodiment 5 of the present invention: A method for preparing a coal rock sheet, wherein the coal sample crushed to a qualified particle size is pre-moistened with a dextrin solution before being mixed with a binder, stirred to fully wet the coal particles, filtered and dried in the shade, and then mixed with the binder, placed in a mold and dried at room temperature, and then ground and polished to prepare a coal rock sheet. 1g of the coal sample is weighed, and 5mL of water and 300mg of dextrin are added accordingly, and the water and dextrin together form a dextrin solution.
[0024] In the above embodiment, the coal sample is firstly crushed to a specified particle size (the coal particles completely pass through a 1.0 mm test sieve, and particles smaller than 0.1 mm do not exceed 10%).
[0025] In order to verify whether the performance of the coal rock optical slice prepared by the method of the present invention is improved, the following test is conducted.
[0026] 1. Test methods
[0027] A total of 3 groups and 7 samples (numbered ag) were prepared. One sample (numbered a) of the first group was prepared by a traditional preparation method, and the remaining two groups (3 samples in each group, numbered b, c, d and e, f, g) were prepared by pretreating the samples with different amounts of water and dextrin solution according to the preparation method of the present invention, and then grinding, polishing and parameter measurement were performed. The amount of water and dextrin used in each sample is shown in Table 1. A laser confocal microscope was used to perform parameter characterization and image characterization of the microscopic morphology of the polished surface of the coal rock light slice, and the characterization parameters were digitized and standardized. For details, see Figure 2 .
[0028] Table 1 Test sample number and test conditions
[0029] Test conditions a b c d e f g Water / (mL / g) 0 0.5 2 5 5 5 5 Dextrin dosage / (mg / g) 0 0 0 0 50 150 300
[0030] The traditional preparation method of coal rock slices is based on the international standard ISO 7404-2:2009 (Methods for petrographic analysis of coal - Part 2: Methods for preparing coal samples) and the national standard GB / T16773-2008 "Standard for the preparation of coal rock analysis samples". The main steps are: (1) crush 1g of representative coal sample to the specified particle size (coal particles completely pass through the 1.0mm test sieve, and particles less than 0.1mm do not exceed 10%); (2) mix with a binder (epoxy resin) in a certain proportion, and press it into a coal rock slice by condensation or heating; (3) for one end face, use 320, 800, 1000, 2000 silicon carbide sandpaper in turn for coarse grinding, fine grinding and fine grinding on a metallographic grinding and polishing machine; (4) polish with red velvet polishing cloth and alumina polishing liquid. After polishing, place it in an ultrasonic cleaner for 2 to 3 minutes to clean the polished surface.
[0031] The method of the present invention is based on the international standard ISO 7404-2:2009 and the national standard GB / T16773-2008 and proposes the following improvements: for the coal sample crushed to a qualified particle size, before mixing with the binder, it is first pre-moistened with water or dextrin solution, fully stirred for a certain period of time, filtered and dried in the shade, and then placed in a mold to mix with the binder, placed in the mold under room temperature conditions, and then ground and polished to prepare a coal rock slice. The preparation process is as follows Figure 1 shown.
[0032] 2. Surface flatness characterization method
[0033] A laser confocal microscope (manufacturer: OLYMPUS CORPORATION, Japan; model: OLS5000; flatness setting information: S filter: 8.000 μm; correlation threshold c: 0.2; filtering: Gaussian; analysis parameters: height / mixed) was used to collect surface morphology images of coal rock light slices under a ×5 objective lens to measure surface parameters.
[0034] 3. Test results
[0035] According to the international standard ISO 25178 on surface roughness evaluation methods, the arithmetic mean height S a It is generally used to evaluate the surface roughness of the selected surface. The smaller the value, the smaller the roughness of the detected surface and the smoother the surface. z It refers to the sum of the maximum peak height and the maximum valley depth in the measured area. If there are a lot of concave and convex surfaces in the detection area, S z Increase. RMS height S q It refers to the standard deviation of the surface height of the measured area, S q The smaller the surface, the smoother the surface. drIt refers to the extent to which the expansion area of the measured area increases relative to the area of the measured area. If the surface is completely flat, then S dr is 0. If there are holes on the surface, S dr Will increase.
[0036] Depend on Figure 2 It can be seen that the S of the coal rock slices prepared by the traditional method is a 61.71μm, S q 106.09μm, S z 802.54μm, S dr The S of the polished surface is 29.83%, and the flatness of the polished surface is poor. a , S q , S z , S dr The amount of water used is an important factor affecting the flatness of the polished surface. When the amount of water is 5 mL / g (sample d), S a 5.86μm, S q 14.25μm, S z 394.67μm, S dr The surface smoothness of the coal rock sheet is better at 21.57%. On the basis of using 5mL / g water for wetting, different amounts of dextrin were added to the water to pre-treat the coal particles. It was found that the surface parameter values of the prepared coal rock sheet were further reduced. When the mass of dextrin added was 150mg, S a 4.30μm, S q 5.49μm, S z 219.65μm, S dr The above test data show that the surface roughness of the coal rock sheet prepared by adding water or dextrin solution to pre-treat the coal particles is reduced and the smoothness is better.
[0037] The above 7 samples were observed by laser confocal microscopy, and the surface morphology features collected were as follows: Figure 3-9 shown.
[0038] Depend on Figure 3 It can be seen that when the polished surface of the coal rock slice prepared without pretreatment is observed under a microscope, the two-dimensional and 3D morphologies of the slice reveal that the surface has many pits and the flatness is not high.
[0039] Depend on Figure 4-Figure 6It can be seen that the polished surface of the coal rock slice made by pre-wetting the coal particles with water has fewer pits and is smoother than the polished surface of the untreated coal rock slice. The 3D morphology and its corresponding morphology contour map show that as the amount of water increases, the depth of the pits on the polished surface of the coal rock slice gradually decreases. When the amount of water is 5mL / g (Figure d), the pits are the shallowest.
[0040] Depend on Figure 7-Figure 9 It can be seen that the smoothness of the polished surface of the coal rock slice prepared after pretreatment of the coal particles with dextrin solution is the best. Different dextrin dosages also affect the quality of the slice. For 1g coal sample, when 5mL / g water and 50mg / g dextrin are used (Figure e), the two-dimensional morphology and 3D morphology of the polished surface and its morphology profile diagram show that the smoothness of the polished surface is improved, but there are still a small number of pits on the surface; when 5mL / g water and 150mg / g dextrin are used (Figure f), the two-dimensional morphology and 3D morphology of the polished surface and its morphology profile diagram show that its smoothness is good and there are no pits on the surface. When 5mL water and 300mg dextrin are used (Figure g), the improvement of the quality of the slice is not obvious.
[0041] 4. Conclusion
[0042] The above results show that the polished surface of the coal rock slices prepared from the untreated coal samples is uneven, and there are a large number of pits of varying depths; for 1g of coal sample, after pre-wetting the coal sample with 5mL of water or a dextrin solution formed by 5mL of water and 150g of dextrin, the polished surface of the coal rock slices obtained is smoother and flatter, with almost no pits, indicating that the pre-wetting treatment of coal particles using this method can effectively improve the quality of coal rock slices.
[0043] Compared with the national standard method, the optical slices prepared by pre-wetting the coal particles with dextrin solution are more stable, with no pits on the polished surface, better flatness, less surface roughness, and clearer boundaries of microscopic components. This method is highly operable and does not affect the properties of coal and rock. The purpose of pre-treatment with dextrin solution is to eliminate the air film on the surface of coal particles, enhance the wettability of the coal particle surface, and fundamentally avoid the presence of bubbles and pits in the optical slices.
Claims
1. A method for preparing a coal rock optical film, characterized in that: For coal samples that have been crushed to a qualified particle size, they are pre-moistened with water or dextrin solution before being mixed with the binder, stirred to fully moisten the coal particles, filtered and dried in the shade, and then mixed with the binder. After being placed in a mold and dried at room temperature, they are ground and polished to prepare coal rock slices.
2. The method for preparing a coal rock optical sheet according to claim 1, characterized in that: When using water to pre-wet the coal sample, weigh 1g of coal sample and add 2 to 5mL of water.
3. The method for preparing a coal rock optical sheet according to claim 2, characterized in that: When water is used to pre-wet the coal sample, 5 mL of water is added for every 1 g of coal sample.
4. The method for preparing a coal rock optical sheet according to claim 1, characterized in that: When the coal sample is pre-moistened with a dextrin solution, 1 g of the coal sample is weighed, and 5 mL of water and 50 to 300 mg of dextrin are added accordingly. The water and dextrin together form a dextrin solution.
5. The method for preparing a coal rock optical film according to claim 4, characterized in that: When the coal sample is pre-moistened with a dextrin solution, 1 g of the coal sample is weighed, and 5 mL of water and 150 mg of dextrin are added accordingly. The water and dextrin together form a dextrin solution.
Citation Information
Patent Citations
Outdoor knitting product anticorrosion paint with characteristic of biological fouling resistance
CN105176322A
Preparation method for micro-fine-grain powder sample polished section
CN108776053A
Coal briquette polishing method
CN108942422A
Deaerating module
WO1999015252A1